Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan : Studi Pada Karyawan PT. Mega Medical Abadi - Saddam Qhintara; Dwi Kristanto (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the Influence of Work Discipline and Work Environment on Employee Performance. The research method used is quantitative descriptive and the data analysis is multiple linear regression. The employee population of PT. Mega Medical Abadi as many as 50. Sampling in this study used saturated sampling using a total of 50 respondents. Data was collected through a questionnaire with a likert scale using Microsoft Excel 2021 Software and SPSS Software Version 25.0. Data were obtained from the questionnaire distribution and obtained from company documentation, annual reports, scientific journals and literature relevant to the research topic. The results of the study show that the Work Discipline variable has a positive and significant effect on Employee Performance, the Work Environment variable has a positive and insignificant effect on Employee Performance, Work Discipline and Work Environment have a simultaneous significant effect on Employee Performance. Data analyst techniques in the study to test validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedastasis test, correlation coefficient test, multiple linear regression analysis test, determination coefficient analysis (R2), simultaneity test (F test), t-test hypothesis test (t test).